Rekontruksi Syari'at Islam (Pemikiran Khalil Abdul Karim Tentang Hubungan Syariat Islam Dan Tradisi Lokal) - Siti Mahmudah (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2011)
Back to read the historical reality of how Islam is derived in the midst of a people known as 'Ignorance' by most people but not for some people who belong to the wise. As figure Khalil Abdul Karim did not want to mention Arabs as the Pre-Islamic Ignorance is the opposite because they are among the civilized and knowledgeable human height. As evidence God has provided a challenge to them so they could create works that are able to match the verses are referred to as the revelation of God in the Qur'an, if not able to do more, it is enough to make comparable with that mentioned in al-Qur 'an as mu'zizat of God bestowed on the Qur'an and entrusted to the Prophet Muhammad. This theory was used by Khalil Abdul Karim in order to answer any conflict between Islamic law that developed in the era of the contemporary world, have no concept of dialogue between Islamic law and local tradition that the two must keep going along in rhythm and in the theory and practice of life community wherever and whenever.